1986
DOI: 10.1111/j.1365-2621.1986.tb10854.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Degree of Pectin Methylation and Tissue Firmness of Cucumber Pickles

Abstract: The relationship between pectin methylation and tissue firmness was examined in cucumber pickles exposed to pre-brining and brining treatments. Tissue treated with CaCI, prior to or during brining, blanched before brining or held at 2°C during brine storage resisted softening. Although all treatments reduced the degree of esterification (DE) of pectic substances, less demethylation occurred in treatments that protected against softening. Join point regression analysis of the data indicated that maximum firmnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 17 publications
3
28
0
1
Order By: Relevance
“…However, some studies reported that PME may not always be associated with firming. McFeeters, Fleming, and Thompson (1985) found no relationship between PME and cucumber tissue firmness and Hudson and Buescher (1986) suggested that excessive demethylation may change the pectin configuration and cause softening by the loosening of cell wall components. To better understand the relationship between observed PME activity and the firming effect induced by HPCD treatments, further studies will need to be conducted.…”
Section: Effect On Hardnessmentioning
confidence: 98%
“…However, some studies reported that PME may not always be associated with firming. McFeeters, Fleming, and Thompson (1985) found no relationship between PME and cucumber tissue firmness and Hudson and Buescher (1986) suggested that excessive demethylation may change the pectin configuration and cause softening by the loosening of cell wall components. To better understand the relationship between observed PME activity and the firming effect induced by HPCD treatments, further studies will need to be conducted.…”
Section: Effect On Hardnessmentioning
confidence: 98%
“…Softening in cucumbers is closely related to the demethylation of pectin by the enzyme pectin methylesterase (PME) [2]. Therefore, PME should be inactivated by blanching to retard the softening of cucumber tissue during storage in brine [3].…”
Section: Introductionmentioning
confidence: 99%
“…Optical and electronic microscopy is frequently used to detect microstructural changes during ripening (LUZA et al, 1992), storage (ALLAN-WOJTAS et al, 2001), refrigerated storage, pre-treatment (SOUSA et al, 2005), drying (LEWICKI; PAWLAK, 2003) and freezing (DELGADO; RUBIOLO, 2005) of plant tissue ( VAN BUGGENHOUT et al, 2008) The use of sugar solutions, hydrocolloids, calcium and sodium salts, and associations and mixtures involving these products, have been the indicated substances treatments that increase cellular structure resistance to freezing. A large part of these compounds act by interacting with the cell wall components, reducing the ice crystal growth and maintaining the integrity of the microstructure after thawing (RESENDE; CAL-VIDAL, 2002).…”
Section: Loss Of Cellular Fluid (Lcf)mentioning
confidence: 99%